ANALISIS MUTU BETON TERHADAP BETON PASCA BAKAR - Bazar Asmawi; Indra Syahrul Fuad; Hendrik Jimmyanto (LATERAL: Jurnal Teknik Sipil, 2023)
A fire is an unwanted disaster, in the framework of a post-fire building structure it becomes the basis for deciding whether the building structure can still be used or not. The rise in high temperatures in concrete structures will result in changes in concrete, the problem faced is how to handle post-fire buildings. From this explanation, this research will discuss the strength of concrete structures, especially the ratio of normal concrete to concrete that has been burnt with variations in duration of burning 1 hour, 2 hours and 3 hours under normal conditions. Concrete compressive strength testing was carried out when the specimens reached the age of 3 days, 7 days, 14 days, 21 days, and 28 days with cylindrical specimens and the flexural strength of concrete was carried out when the specimens reached 28 days. The number of concrete compressive strength test specimens is 36 unit, and the flexural strength is 12 unit. The normal quality of concrete used is 30 MPa. From the results of the analysis regarding the tests carried out on compressive strength, it can be concluded that from the results of the compressive strength tests of 1 hour, 2 hours and 3 hours it decreased by 26.83%, 41.46% and 59.67% compared to concrete normal, for the flexural strength test results of 1 hour, 2 hours, and 3 hours decreased by 33.25%, 66.75%, and 66.75% compared to normal concrete.